Impact of Gravity on Thyroid Cells - Albi, Elisabetta (Int J Mol Sci, 2017)
Physical and mental health requires a correct functioning of the thyroid gland, which controls cardiovascular, musculoskeletal, nervous, and immune systems, and affects behavior and cognitive functions. Microgravity, as occurs during space missions, induces morphological and functional changes within the thyroid gland. Here, we review relevant experiments exposing cell cultures (normal and cancer thyroid cells) to simulated and real microgravity, as well as wild-type and transgenic mice to hypergravity and spaceflight conditions. Well-known mechanisms of damage are presented and new ones, such as changes of gene expression for extracellular matrix and cytoskeleton proteins, thyrocyte phenotype, sensitivity of thyrocytes to thyrotropin due to thyrotropin receptor modification, parafollicular cells and calcitonin production, sphingomyelin metabolism, and the expression and movement of cancer molecules from thyrocytes to colloids are highlighted. The identification of new mechanisms of thyroid injury is essential for the development of countermeasures, both on the ground and in space, against thyroid cancer. We also address the question whether normal and cancer cells show a different sensitivity concerning changes of environmental conditions.